Pengaruh Kepemimpinan Kepala Sekolah dan Motivasi Guru Terhadap Profesionalisme Guru SMP Islam Daarul Ilmi - Fachru Abdul Rahman; Raharjo (Jurnal Dirosah Islamiyah, 2024)
The problem of this research is that some teachers have not shown good performance in carrying out their duties and functions, meaning that they are in accordance with the main duties and functions of teachers, such as: activities in planning teaching programs, carrying out learning activities, carrying out assessments, carrying out daily tests, preparing and implementing improvement programs. and enrichment as well as developing the field of teaching for which he is responsible. As an illustration of the profile of teachers whose performance is still low, these include: teachers teaching monotonously and without thorough preparation. Teachers still use very simple teaching preparation, have not fully used the required curriculum references, and are inconsistent in implementing the lesson plan (RPP) scenarios that have been prepared and in the learning process teachers still predominantly use the lecture method. The objectives are (1) to determine the influence the principal's leadership towards teacher professionalism; (2) To determine the effect of teacher motivation on teacher professionalism; and (3) determine the influence of the principal's leadership and teacher motivation on the professionalism of Daarul Ilmi Rancabungur Islamic Middle School teachers. Researchers used quantitative descriptive methods, because the research was carried out by analyzing numerical data (numbers). Meanwhile, the sampling technique uses Cluster sampling (Area Sampling). The population of this study was all Daarul Ilmi Islamic Middle School teachers, totaling 50 people with a population of 50 teachers determined through a purposive sampling technique. The data collection method used was a questionnaire. From the research results, it can be seen from hypothesis testing that: (1) there is a positive and significant influence of principal leadership on teacher professionalism by 22.3%, (2) there is a positive and significant influence of teacher motivation on teacher professionalism by 17.3%, ( 3) there is a positive and significant influence of the principal's leadership and teacher motivation on teacher professionalism of 28.9%. This positive influence means that if the principal's leadership and teacher motivation on teacher professionalism are good then teacher professionalism will increase.